Constructions of intersubjectivity : discourse, syntax, and cognition - Verhagen, Arie (OUP E-Books., 2005)
Arie Verhagen develops a new understanding of linguistic communication focussed on cognition. He treats pragmatics, semantics, and syntax in parallel and integrates insights from linguistics, psychology, and animal communication. He shows the continuity between language and animal communication and reveals the nature of human linguistic specialization. His powerfully argued and original explanation of the nature and operation of communication will interest a wide range of scholars. and advanced students in linguistics, cognitive science, and human evolution. - ;Constructions of Intersubjectivi.